PENGARUH SELF TALK MOTIVASI DAN COMANDO TERHADAP HASIL SMASH ATLET CLUB BULUTANGKIS ABC BANDUNG - Puja Adria Ramadhan, - (2023)
This study aims to examine the effect of self-talk motivational and commando exercises on the smash results of athletes at the ABC Bandung badminton club. The method used in this study is an experimental method with a two-group pretest-posttest design. The sample of this study were 10 athletes of the ABC Bandung badminton club and the population sampling technique used the purposive sampling technique which was then divided into 2 equal groups, namely the experimental group and the control group. The experimental group was commando self-talk, while the control group was motivational self-talk. This research was given for 12 meetings. The instrument given was in the form of a smash skill test which was given twice (pretest and posttest). Data analysis used the t test while the normality test used the Shapiro-Wilk. The results showed that motivational Self talk exercises had a change of 22.57% and for commando had a change of 37.09%. This research shows that motivational and commando self-talk exercises have changed, but commando self-talk exercises have a significant effect on the smash results of athletes at the ABC Bandung badminton club. Keywords : Motivational self-talk, comado self-talk, smash and badminton